A Convenient Synthesis of N,N-Dimethylformamidines from Sulfonamides - Chen, Yantao; Gradén, Henrik; Aurell, Carl-Johan; Gibson, James (Synthesis, 2015)
N,N-Dimethylformamidines were synthesized from sulfonamides using the Vilsmeier reagent as a cleavage activator. The reactions were performed under mild conditions achieving good to excellent yields. The chemistry presented can also be used as a deprotection strategy when amines or anilines are protected with sulfonyl groups, such as the tosyl group.
Keywords: sulfonamides; cleavage; imines; nucleophilic addition; amines; hydrolysis